BiVO4 nanofiber-based field-effect transistors for detection of epinephrine/adrenaline hormones. (4th November 2021) - Veeralingam, Sushmitha; Badhulika, Sushmee
Abstract : In this work, an ultrasensitive-BioFET (biosensor field-effect transistor) is developed for chemiresistive, label-free detection of epinephrine hormone in urine samples. Abstract : In this work, an ultrasensitive-BioFET (biosensor field-effect transistor) is developed for chemiresistive, label-free detection of epinephrine hormone in urine samples. Flexible surface oxidized aluminium foil is used as a substrate. BiVO4 nanofibers fabricated using a facile electrospinning technique act as an electroactive n-type semiconductor-channel deposited over thermally evaporated Cr/Ti metal contacts (source and drain terminals). The floating-gate terminal is coupled to the sensing area where epinephrine molecules are adsorbed. Detailed characterization studies reveal the formation of monoclinic-phase, 1D (1- dimensional) large surface area BiVO4 nanofibers with an average diameter of 40 ± 5 nm. The BioFET exhibits a transconductance and mobility of 2.8 μS and 5.23 cm 2 V −1 s −1, respectively. The biosensor exhibits a sensitivity of 115.2 nM −1 in the sensing range of 25 nM–50 μM and 48.3 nM −1 for concentrations ranging from 0.5–25 nM with a LOD of 0.34 nM (3 S / m ). The fabricated BioFET exhibited a rapid response time of 0.2 s. The sensing mechanism is explained via a combination of electrostatic gating and Schottky barrier effects. BioFET demonstrated excellent stability, reproducibility, and selectivity towards epinephrine in the presence of interfering species due to the selective binding of aromatic amine with the BiVO4 nanofibers. The practicability of the sensor was tested using a test matrix of urine samples. The BioFET proves to be a reliable platform for the detection of macromolecules for point-of-care diagnostics.